2023
DOI: 10.1021/jacs.2c08853
|View full text |Cite
|
Sign up to set email alerts
|

Sulfamate Acetamides as Self-Immolative Electrophiles for Covalent Ligand-Directed Release Chemistry

Abstract: Electrophiles for covalent inhibitors that are suitable for in vivo administration are rare. While acrylamides are prevalent in FDA-approved covalent drugs, chloroacetamides are considered too reactive for such purposes. We report sulfamate-based electrophiles that maintain chloroacetamide-like geometry with tunable reactivity. In the context of the BTK inhibitor ibrutinib, sulfamate analogues showed low reactivity with comparable potency in protein labeling, in vitro, and cellular kinase activity assays and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…The London group explored alternative α-LGs beyond halides after encountering problems with the replacement of a CA in their PIN1 (peptidyl-prolyl cis−trans isomerase, NIMA-interacting 1) chemical probe sulfopin 32 (54, Figure 17) and to expand upon their concept of CoLDR chemistry. 153 They compared The utility of sulfamate acetamides as TCI warheads could be shown by synthesis of ibrutinib sulfamate acetamide derivatives through late-stage functionalization. These derivatives, exemplified by N-methyl sulfamate 55c and its sulfone and sulfonate analogs (55a,b, Figure 17), exhibited similar reactivity patterns as the model compounds.…”
Section: Cysteine Addition To Alkenyl-or Alkynyl-substituted Heteroar...mentioning
confidence: 99%
“…The London group explored alternative α-LGs beyond halides after encountering problems with the replacement of a CA in their PIN1 (peptidyl-prolyl cis−trans isomerase, NIMA-interacting 1) chemical probe sulfopin 32 (54, Figure 17) and to expand upon their concept of CoLDR chemistry. 153 They compared The utility of sulfamate acetamides as TCI warheads could be shown by synthesis of ibrutinib sulfamate acetamide derivatives through late-stage functionalization. These derivatives, exemplified by N-methyl sulfamate 55c and its sulfone and sulfonate analogs (55a,b, Figure 17), exhibited similar reactivity patterns as the model compounds.…”
Section: Cysteine Addition To Alkenyl-or Alkynyl-substituted Heteroar...mentioning
confidence: 99%
“…We also found that the CFA–thiol adducts undergo reverse hydrolysis under neutral aqueous conditions, which could contribute to eliminating off-target protein labeling. A few covalent inhibitors bearing a dichloroacetamide (DCA) as a cysteine-reactive warhead have also been reported. , More recently, sulfamate acetamides have been identified as cysteine-targeting electrophiles with chloroacetamide-like reaction geometry . Despite such active situations, systematic studies of the reactivity profile of the haloacetyl compounds have scarcely been documented in the literature …”
Section: Introductionmentioning
confidence: 99%
“…51,52 More recently, sulfamate acetamides have been identified as cysteinetargeting electrophiles with chloroacetamide-like reaction geometry. 53 Despite such active situations, systematic studies of the reactivity profile of the haloacetyl compounds have scarcely been documented in the literature. 54 Here, we report a systematic survey of reactivity profiles of a series of haloacetamides toward cysteine thiol.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The recent successes in the development of targeted covalent inhibitors (TCIs), including afatinib, ibrutinib, and sotorasib, have spurred renewed interest in irreversible protein inhibition as a drug design strategy. TCIs generally consist of two components: a ligand that selectively and reversibly binds to the target protein and an electrophilic warhead that can form a covalent bond with an amino acid residue near the ligand-binding site through proximity-induced acceleration of the reaction rate. , The resulting covalent drug–protein complex does not dissociate, leading to increased potency and an extended duration of action. Most conventional TCIs, including the aforementioned approved drugs, exploit the high nucleophilicity of cysteine side chains for the reaction site, and Michael acceptors have been widely employed as the warheads. ,, Despite numerous successes, such a cysteine-dependent drug design has several limitations. For example, this method cannot be applied to the majority of proteins that do not have cysteine residues near the druggable binding site.…”
Section: Introductionmentioning
confidence: 99%